2022
DOI: 10.3390/ijms23158354
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Induced Mutagenesis of TMS5 Confers Thermosensitive Genic Male Sterility by Influencing Protein Expression in Rice (Oryza sativa L.)

Abstract: The development of thermosensitive genic male sterile (TGMS) lines is the key to breeding two-line hybrid rice, which has been widely applied in China to increase grain yield. CRISPR/Cas9 has been widely used in genome editing to create novel mutants in rice. In the present study, a super grain quality line, GXU 47, was used to generate a new TGMS line with specific mutations in a major TGMS gene tms5 generated with CRISPR/Cas9-mediated genome editing in order to improve the rice quality of two-line hybrids. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…(Huang et al, 2014). Recent studies revealed the molecular mechanism of tms5 leading to male sterility in rice to easily obtain excellent TGMS lines (Fang et al, 2022) and potentially applicable in other crops. CRISPR/Cas9-engineered mutation of TMS5 also resulted in the formation of thermosensitive male sterility in maize (Li et al, 2017).…”
Section: Environmental Genic Male Sterilitymentioning
confidence: 99%
“…(Huang et al, 2014). Recent studies revealed the molecular mechanism of tms5 leading to male sterility in rice to easily obtain excellent TGMS lines (Fang et al, 2022) and potentially applicable in other crops. CRISPR/Cas9-engineered mutation of TMS5 also resulted in the formation of thermosensitive male sterility in maize (Li et al, 2017).…”
Section: Environmental Genic Male Sterilitymentioning
confidence: 99%
“…Many male-sterile-related genes have been well characterized in maize [100], rice [101][102][103][104][105], wheat [106], and soybean [107], and improved the understanding of the molecular mechanisms that control male sterility in crops. Importantly, increasing CRISPR-edited malesterile lines have been generated in maize by knocking out ZmMS26 or ms8 [108,109], rice by editing TMS5, OsOPR7, or CYP703A3 [99,[110][111][112][113][114][115], wheat by targeting TaNP1, Ms1, or Ms45 [116][117][118], foxtail millet [119], and soybean [120]. Thus, the CRISPR/Cas technology has provided a powerful tool for the generation of male-sterile lines and will greatly promote commercial hybrid seed production in different crops.…”
Section: Accelerating Conventional Production Of Crop Hybrid Seedmentioning
confidence: 99%